Beyond Information Costs: Preference Formation and the Architecture of Property Law. (10th February 2020) - Zhang, Taisu
Abstract: Contemporary property theory highlights information costs as the central determinant of exclusion rights and numerus clausus-type standardization: rising information costs lead to stronger exclusion rights and more standardization, whereas falling information costs have the opposite effect. This paradigmatic model lacks, however, a theory of how information costs change in the first place. By developing such a theory, this article demonstrates that, in prominent cases, the legal impact of information costs tends to be counterbalanced by concurrent changes in individual preference, and that preexisting predictions about the relationship between information costs, standardization, and exclusion are therefore partially wrong, and otherwise incomplete.